Heterometallic Pentanuclear [Ni4Ln] (LnIII = Gd, Tb, Dy, Ho) Complexes: Accidental Orthogonality Leading to Ferromagnetic Interactions. Issue 21 (16th June 2014) - Das, Sourav; Hossain, Sakiat; Dey, Atanu; Biswas, Sourav; Pardo, Emilio; Lloret, Francesc; Chandrasekhar, Vadapalli
Abstract: The reaction of 6‐formyl‐2‐(hydroxymethyl)‐4‐methylphenol (LH2 ) with Ni II and Ln III salts afforded a series of heterometallic pentanuclear compounds [Ni4 Ln(L)4 (OAc)2 (MeOH)4 ](NO3 )(MeOH) [Ln III = Gd (1 ), Dy (2 ), Tb (3 ), Ho (4 )]. Four dianionic L 2– ligands and two acetate anions hold together four Ni II and one Ln III ion to form a Ni4 Ln core possessing a distorted tetrahedral geometry. All the Ni II ions are hexacoordinate (6 O) with a distorted octahedral geometry whereas the Ln III ion is octacoordinate (8 O) with a distorted square‐antiprism geometry. All the Ni II ions are connected to the central Ln III ion through μ2 bridging of one deprotonated phenolic oxygen and two deprotonated alkoxy oxygen atoms. The magnetic properties of1 –4 were investigated in the temperature range 2–300 K. The magnetic properties of1 were fitted by using a Hamiltonian containing isotropic exchange, Ni II local zero‐field‐splitting, and Zeeman effects ( Ĥ = Ĥ exchange + Ĥ zfs + Ĥ zeeman ). The molecular structures of1 –4 reveal that the Ni–O–Ln angle is around 89° whereas the Ni–O–Ni angle is about 96°. Because of this accidental orthogonality, ferromagnetic interactions between the nearest‐neighbor Ni II ions and between Ni II and Ln III ions have been observed. The observed J values are 0.34 and 1.88 cm –1 between Gd III –Ni II and Ni II –Ni II, respectively. Abstract : The reaction of 6‐formyl‐2‐(hydroxymethyl)‐4‐methylphenol with appropriate lanthanide salts followed by reaction with Ni(OAc)2 · 4H2 O affords pentanuclear heterobimetallic compounds containing a [Ni4 Ln] core. These complexes have a distorted tetragonal core structure in which the M–O–M′ (M′ = Ni II /Ln III ) angles are around 90°.